The Islamic Values of Karaton Ngayogyakarta Hadiningrat Culture (Anthropological Perspective of Islamic Education) - M. Sayyidul Abrori; Ikhwan Aziz; M. Zainal Arifin; Dedi Setiawan; Suwanto (Edukasia Islamika : Jurnal Pendidikan Islam, 2022)
The focus of writing the text Values ​​at the Ngayogyakarta Hadiningrat Palace is on the influence of modernization, liberalization, democracy, radicalism, terrorism, and other understandings that can result in discrimination against local cultural values. Thus, there is a need to understand historical heritage in the form of traditions and artifacts that contain philosophy or idioms related to Islamic values on local culture. This type of research is field research using a qualitative analysis study and a scientific approach to Islamic education anthropology. Sources of data are penghageng and courtiers of the Ngayogyakarta Palace. It is collecting data through non-participant observation, documentation, and interviews. The results of this study include: 1) Internalization of Islamic values ​​in the cultural ideas of the Ngayogyakarta Palace is shown through the elaboration of the Sultan's nobility title, which has the concept of prophetic leadership leader and the Sultan's responsibility to provide welfare and security for the people. 2) Internalization of Islamic values ​​in the cultural activities of the Ngayogyakarta Palace is shown through Islamic values ​​in the tradition Garebeg as a ceremony to Kanjeng Prophet Muhammad SAW to be able to get intercession on the last day through a ceremony carried out by sharing food with the people with the intention of the Sultan giving charity to the people. 3) Internalization of Islamic values ​​in the cultural works of the Ngayogyakarta Palace, which are reviewed through the palace building, the plants around the palace, and the layout of the Ngayogyakarta.